Soil Condition and Vegetal Cover in the Eroded Banks of the River 'Jumar' at Kanke (Ranchi). - Singh, B. N; Chatterjee, B. N.; Das, N.C. (Journal of Soil and Water Conservation, 2022)
The soil conditions and the vegetal cover along the slopes, on the eroded banks of river Jumar by the side of the Ranchi Agricultural College Farm, was studied. After contour survey, the area was broadly divided into 10 blocks according to slopes (ranging from 0-1% to 6—7% Soil and Negetational analysis in these blocks were done in four replicates along the slope.It was observed that the blocks differed widely in their contents of nitrogen (ranging from 0.009 to 0. 122%), organic carbon (0.028 to 1.120%), water holding capacity (26 to 44%), field moisture (6 to 20%) during February, clay (3 to 32%) and in the develop- ment of plant communities (mostly grasses) in each block. The pH values ranged from 5.48 to 7.08.Apart from the variations in soil and vegetation between blocks there were also significant differences within the blocks along the slopes. When this was analysed it further revealed that in general, there have been significant in nitrogen, clay and reductions, upslopes, field moisture. Consequent to the changes in the edaphic condition, up the slopes, there had been differences in the pattern of distribution of some important grasses at the site. The population per unit area of Ischaemurn rugosum was more at places having more nitrogen, organic carbon, clay and water holding capacity under adequate moisture. Heteropogon contortus predominating at the top most slopy block and Saccharum spontanewn predominating in the sandy soil by the side of the river showed negative associations with clay and water holding capacity. The population of Panicum repens increased, with the increase in moisture status and decrease in the clay percentage of the soil. Imperata cylindrica predominated in loamy sand and gaacly loam soils, very close to the river. Dichanthium annulatum was rather widely distributed except in very wet and sandy soils; thus showing wider adaptability than others.